Planificación e implementación parcial del sistema de gestión de la calidad en la empresa diseños Punto de Oro Ltda (2009)
Diseños Punto de Oro Ltda. is a private company in the production and commercialization of ties; the company began the planning and partial implementation of the quality managment system, in accordance with ISO 9001:2000. The frequent variation in the quality of ties between each batch of production was the problem to solve. There was obstacles in the project, wich was overcome by the team and were great learning to be shared in this article